2014
DOI: 10.1371/journal.pone.0095055
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 and Interleukin-33 Levels in Coronary Artery Disease: Relation to Disease Activity and Adverse Outcome

Abstract: ObjectivesST2 is a receptor for interleukin (IL)-33. We investigated an association of soluble ST2 (sST2) and IL-33 serum levels with different clinical stages of coronary artery disease. We assessed the predictive value of sST2 and IL-33 in patients with stable angina, non-ST elevation myocardial infarction (NSTEMI) and ST elevation myocardial infarction (STEMI).MethodsWe included 373 patients of whom 178 had stable angina, 97 had NSTEMI, and 98 had STEMI. Patients were followed for a mean of 43 months. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 33 publications
5
80
0
4
Order By: Relevance
“…14 No difference in severity of the disease with respect to angiographic findings in present study. Patients with STEMI showed the highest serum levels of soluble ST-2 in a study performed by Demyanets S et al 20 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…14 No difference in severity of the disease with respect to angiographic findings in present study. Patients with STEMI showed the highest serum levels of soluble ST-2 in a study performed by Demyanets S et al 20 …”
Section: Discussionmentioning
confidence: 90%
“…In contrast most of the other studies have used R&D systems. 3,20 In present study the blood sample was collected within 48 hours after onset of MI. There is considerable variation in the timing of sample collected in the earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an association between worse cardiovascular outcome and increased TNF-α [23] and IL-6 [24][25][26] levels specifically following an acute coronary syndrome (ACS). However, despite their anti-inflammatory properties during MI, both IL-33 [27,28] and TGF-β [29] have been found to be associated with a worse prognosis in coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…They found that sST2 levels were significantly increased in patients with ACS as compared to patients with stable coronary artery disease and control individuals without significant stenosis on coronary angiography (44). The same research group showed that the level of circulating sST2 is associated with the stage of coronary artery disease and is increased continuously from stable coronary artery disease to NSTEMI and STEMI.…”
Section: St2mentioning
confidence: 95%